Klausula Baku Dalam Perjanjian Kredit Tanpa Agunan Di Bank Permata; Studi Penerapan Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen - Muhammad Fachri Akbar; Nurhasanah Nurhasanah (JOURNAL of LEGAL RESEARCH, 2019)
AbstractThis study aims to analyze the standard clauses in loan agreements without collateral in terms of consumer protection laws using the principles of the law approach and the theory of legal effectiveness. In addition, it aims to determine the response of credit users without collateral for the standard clause. The method used in this study is the Normative Law Research method. Normative Legal Research is a literature study using a statutory approach and a conceptual approach. This type of qualitative research requires a sample interview with several informants (credit users). The results of this study outline state that the standard clauses contained in the agreement to apply for Unsecured Loans at Permata Bank there are several points that violate the provisions regarding the standard clauses that have been stipulated in Law Number 8 of 1999 Concerning Consumer Protection and Article 14 of the Regulations Bank Indonesia Number 16/1 / PBI / 2014 Regarding Consumer Protection for Payment System Services.Keywords: Standard Clause, Unsecured Loans, Agreements, Contracts